2009
DOI: 10.4142/jvs.2009.10.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Role of protease inhibitors and acylation stimulating protein in the adipogenesis in 3T3-L1 cells

Abstract: Treatment of AIDS (HIV) and hepatitis C virus needs protease inhibitors (PI) to prevent viral replication. Uses of PI in therapy are usually associated with a decrease in body weight and dyslipidemia. Acylation stimulating protein (ASP) is a protein synthesized in adipocytes to increase triglycerides biosynthesis, for that the relation of PI and ASP to adipogenesis is tested in this work. ASP expression was increased during 3T3-L1 differentiation and reached a peak at day 8 with cell maturation. Addition of PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…This is in concordance with previous data [26][27][28][29], but we also found that the differentiation levels varied at the two study points depending on the insulin used to induce the adipogenesis.…”
Section: Discussionsupporting
confidence: 94%
“…This is in concordance with previous data [26][27][28][29], but we also found that the differentiation levels varied at the two study points depending on the insulin used to induce the adipogenesis.…”
Section: Discussionsupporting
confidence: 94%
“…Forced expression of NEDD8 decreased the expression of C/EBP and PPAR , possibly acting on the differentiation program throughout the NEDD8/p27/beta-catenin pathway [30]. PIs also altered protein expression of two proteins involved in lipid droplet formation, ASP (acylation stimulating protein) [57] and perilipin [58].…”
Section: Introduction: Early Occurrence Of Lipodystrophy After Art Inmentioning
confidence: 96%